Językowe odniesienia do zmysłu wzroku w korespondencji prasowej o modzie z XIX wieku = Linguistic references to the sense of sight in a press correspondence about fashion from the late nineteenth century - Jurewicz-Nowak, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to discuss the function of predicates expressing visual perception used in press correspondence for women from the second half of the 19th century. The research material comes from the "Tygodnik Mód i Powieści" from the years 1895-1900. The study uses the method of interpretive frames, which allows determining the way the predicates of visual perception are presented by the sender, and then place them within specific communication strategies.
Keywords: czasowniki percepcji wzrokowej; metoda ram interpretacyjnych; kognitywizm; strategia komunikacyjna; korespondencja prasowa; fenomen mody; verbs of visual perception; interpretative frame method; cognitivism; communication strategy; press correspondence; fashion phenomenon